2018
DOI: 10.1002/jcp.26459
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of distal ischemic treatment on apoptosis and mitochondrial permeability in the hippocampus after cardiopulmonary resuscitation

Abstract: Apoptosis and mitochondrial dysfunction are the main cause of neurological injury after cardiopulmonary resuscitation (CPR). However, the effects of distal ischemic treatments on ischemia induced apoptosis are rarely studied, and the mechanism by which mitochondrial dysfunction contributes to CPR still unclear. A rat model of distal ischemia was established by clipping the right femoral artery. Rats were divided into blank, model, pre distal ischemic treatment, per-treatment, and post-treatment groups. Neurolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…In this study, the method of clamping and opening the femoral artery was used to complete the remote ischemic post-conditioning treatment. Our results showed that it can reduce neuronal apoptosis after CPR and improve neurological deficit scores in rats, which is consistent with many related studies (26)(27)(28). However, its endogenous protection mechanism needs further study.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the method of clamping and opening the femoral artery was used to complete the remote ischemic post-conditioning treatment. Our results showed that it can reduce neuronal apoptosis after CPR and improve neurological deficit scores in rats, which is consistent with many related studies (26)(27)(28). However, its endogenous protection mechanism needs further study.…”
Section: Discussionsupporting
confidence: 91%
“…When ROS are overproduced, oxidative stress responses in hippocampal neurons are increased and can lead to apoptosis (29,30). Apoptosis of hippocampal neurons is an important mechanism that maintains homeostasis in the brain, and mitochondrial apoptosis is one of the important pathways in this process (31). Increased activity and expression of caspase-3 and caspase-9 are considered markers of mitochondrial apoptotic pathways activity (32).…”
Section: Discussionmentioning
confidence: 99%
“…Later, we tested the opening degree of the MPTP using the MPTP Detection Kit (Beyotime Biotech, China), following specific instructions ( http://www.beyotime.com/index.htm ). Flow cytometry was used to analyze the MMP and MPTP opened of the macrophages derived from peripheral blood [ 27 29 ].…”
Section: Methodsmentioning
confidence: 99%